STRATEGI PENGEMBANGAN EKOWISATA BUKIT BATU, DUSUN SUNGAI LUAR, DESA TIWINGAN BARU, KECAMATAN ARANIO, KABUPATEN BANJAR, PROVINSI KALIMANTAN SELATAN - Rathomy, M. Aditya; Achmad, Basir; Mahreda, Emmy Sri; Febrianty, Irma (Universitas Lambung Mangkurat, 2024)
This research aims to determine what strategies can be taken in managing Bukit Batu Ecotourism. This is because Bukit Batu Ecotourism has considerable potential, including biotic potential such as flora and fauna as well as abiotic potential such as mountains, hills, rivers, forests and lakes which of course have an attraction for tourists. The analytical method used in this research is a qualitative descriptive method. Where this research activity was carried out in natural and uncontrived object conditions, then the data obtained was analyzed using SWOT analysis. the SO strategy in order of priority which is described as follows: (1) Create tourist attractions and attractions that display ecological potential and diversity of flora and fauna such asaviary (giant bird cages), a mini zoo, an aquarium that accommodates local fish species and a miniature Borneo rainforest featuring endemic plant species. (2) Make a viewing tower to enjoy the beautylandscape mountains and lakes as a whole. (3) Empowering the surrounding community in managing Ecotourism such as retribution officers, cleaning officers and security officers. (4) Make plans for the development of facilities and infrastructure based on the most important priorities, such as telecommunication and internet signal booster towers, repair of roads that are still damaged and street lighting. (5) Increase safety warning boards. And (6) Empowerment of BUMDES (Village-Owned Enterprises) with clear work contracts so that they can have an impact on increasing the economy of the surrounding community, such as providing boat rental services, tour guides, bicycle/tent rental and selling souvenirs.